2020
DOI: 10.1001/jamanetworkopen.2020.27315
|View full text |Cite
|
Sign up to set email alerts
|

US Clinicians’ Experiences and Perspectives on Resource Limitation and Patient Care During the COVID-19 Pandemic

Abstract: Key Points Question How have US clinicians planned for and responded to resource limitation during the coronavirus disease 2019 pandemic? Findings This qualitative study included interviews with 61 clinicians across the United States. While institutions planned for an explicit and systematic approach to resource allocation in crisis settings, this approach did not address many challenges encountered by frontline clinicians, leaving them to struggle with wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
132
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 36 publications
3
132
0
2
Order By: Relevance
“…A recent study has shown that clinicians and clinical teams for COVID-19 patient care had struggled with the complexity of providing high-quality care because of the following di culties: crisis capacity, resource limitation, and multiple unprecedented barriers to care delivery. [6,7] In addition, healthcare workers had a higher prevalence of stress, anxiety, depression, and psychological distress than the general population during the COVID-19 pandemic. [8] We hypothesize that additional burdens of nursing care for elderly patients will reinforce the anxiety and exhaustion of medical staff and healthcare resources in the ageing society such as Japan.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that clinicians and clinical teams for COVID-19 patient care had struggled with the complexity of providing high-quality care because of the following di culties: crisis capacity, resource limitation, and multiple unprecedented barriers to care delivery. [6,7] In addition, healthcare workers had a higher prevalence of stress, anxiety, depression, and psychological distress than the general population during the COVID-19 pandemic. [8] We hypothesize that additional burdens of nursing care for elderly patients will reinforce the anxiety and exhaustion of medical staff and healthcare resources in the ageing society such as Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Mitigating strategies to reduce propagation of the pandemic centered on wearing masks, social distancing, and timely testing [1] , [2] . However, the United States had insufficient capacity for rapid SARS-CoV-2 testing that would reduce public health risk and elucidate the true burden of infection [3] [5] . Consequently, the National Institutes of Health (NIH) received an appropriation from Congress in April 2020 to increase the United States capacity to conduct SARS-CoV-2 viral antigen and nucleic acid testing [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Further, when resources cannot fully meet demand, HCWs may experience moral distress due to rationing decisions. [3] In addition, being confronted with a highly contagious pathogen like the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), there is also the fear of becoming infected oneself or spreading the infection to one's family (see Table 1). [4] This stress may contribute to physical exhaustion and feelings of fear and anxiety, sleepdisorders and insomnia, or even burnout and depression.…”
mentioning
confidence: 99%
“…Physically stressful working conditions and witnessing the suffering and death of large numbers of patients take a toll. Further, when resources cannot fully meet demand, HCWs may experience moral distress due to rationing decisions [ 3 ]. In addition, being confronted with a highly contagious pathogen like the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), there is also the fear of becoming infected oneself or spreading the infection to one's family (see table 1 ) [ 4 ].…”
mentioning
confidence: 99%